PERAN DIREKTORAT KEPOLISIAN PERAIRAN DAN UDARA DALAM MENINGKATKAN PATROLI UDARA - Budi Prasetyo; Supri Abu; Martinus Martinus (Strategi Pertahanan Udara, 2023)
This research is motivated by the fact that apart from being used as a positive means, the waters of South Kalimantan also have great potential for various illegal activities and violations, such as illegal fishing, theft by weighting and also including the potential for related criminal acts. with transnational crime, this study uses a qualitative approach with descriptive analytical methods supported by interviews, literature studies, and observation as a method of tracing data and facts, where based on the results of the research it is known that based on the potential threats it can be assumed that the territorial waters have threats with a security dimension which will affect Kamtibmas. These various potential threats can basically be minimized by optimizing water patrols which are one of the main tasks of the South Kalimantan Regional Police Ditpolairud, but with the limited infrastructure of Patrol Boats, the use of the air element in water patrols is one aspect that can be used in these waters